DISCRIMINATION TOWARDS DR. DON SHIRLEY AND TONY LIP AS THE MAIN CHARACTERS AS PORTRAYED IN GREEN BOOK FILM - Rahmawati, Santi; Kuncara, Singgih Daru; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
ABSTRACT In this research, the researcher analyzed the discrimination based on a true story. The researcher only analyzed and discussed the discrimination that happened to the main characters. They are Dr. Don Shirley (African-American) and Tony Lip (Italian-American). The purposes of this research are to identify and describe the types of discrimination that happened to Dr. Don Shirley and Tony Lip and to understand their responses against it. The researcher used theories types of discrimination and types of responses against discrimination declared by Feagin. To analyze this research, the researcher used qualitative research and mimetic approach in this research. Based on the analysis, the researcher found out that all the types of discrimination happened in this film. It also appeared that all the types of responses against discrimination were found in this film. The discrimination in this film was done by both white and black people against Dr. Don Shirley (African-American) and also was done by white people against Tony Lip (Italian-American). The analysis also showed that at first, Tony Lip also discriminated Dr. Don Shirley. Hence, at the end of the film, the analysis showed that Tony Lip has changed. He became more tolerant towards Dr. Don Shirley and stopped discriminating against him. Key words: discrimination, race, African-American, Italian-American ABSTRAK Dalam penelitian ini, peneliti menganalisis diskriminasi berdasarkan kisah nyata. Peneliti hanya menganalisis dan mendiskusikan diskriminasi yang terjadi pada karakter utama. Mereka adalah Dr. Don Shirley (Afrika-Amerika) dan Tony Lip (Italia-Amerika). Tujuan dari penelitian ini adalah untuk mengidentifikasi dan menggambarkan tipe diskriminasi yang terjadi pada Dr. Don Shirley dan Tony Lip dan untuk memahami tanggapan mereka terhadapnya. Peneliti menggunakan teori-teori tipe diskriminasi dan tipe tanggapan terhadap diskriminasi yang dinyatakan oleh Feagin. Untuk menganalisis penelitian ini, peneliti menggunakan penelitian kualitatif dan pendekatan mimetik dalam penelitian ini. Berdasarkan analisis, peneliti menemukan bahwa semua tipe diskriminasi terjadi dalam film ini. Tampaknya semua tipe tanggapan terhadap diskriminasi juga ditemukan dalam film ini. Diskriminasi dalam film ini dilakukan oleh orang kulit putih dan kulit hitam terhadap Dr. Don Shirley (Afrika-Amerika) dan juga dilakukan oleh orang kulit putih terhadap Tony Lip (Italia-Amerika). Pada analisis juga menunjukkan bahwa pada awalnya, Tony Lip juga mendiskriminasi Dr. Don Shirley. Namun, di akhir film, pada analisis menunjukkan bahwa Tony Lip telah berubah. Dia menjadi lebih toleran terhadap Dr. Don Shirley dan berhenti mendiskriminasinya. Kata kunci: diskriminasi, ras, Afrika-Amerika, Italia-Amerika